Life cycle assessment of vegetable oil production: a case study of an oil mill in Ibadan, Nigeria (2014)
The gate-to-gate study aimed to evaluate the potential environmental impacts associated with the production of vegetable oil and to proffer ways of improving and reducing some of the environmental impacts associated with the production system. This study compared the Life Cycle Impact Assessment (LCIA) of four scenarios; different transportation distances for palm kernel materials and different type of fuel used in the boiler. The LCIA was conducted using Gabi 6 and Tool for the Reduction and Assessment of Chemical and other Environmental Impacts (TRACI) methodology. Overall energy consumption in the crushing plant was 34,647.77 MJ and energy consumption in the refining plant was 23,371.65 MJ. Global Warming Potential (GWP) was from 0.0771 kg CO2-equiv., to 0.0763 kg CO2- equiv. for all scenarios. Acidification Potential (AP) values for the four scenarios were: 0.0493 kg H+, 0.0478 kg H+, 0.0476 kg H+ and 0.0492 kg H+ moles-equiv. Eutrophication Potentials (EP), were 6.796E-5 kg N-, 4.88E-5 N-,6.726E-5 N- and 4.905E-5 N-equiv. for scenarios 1, 2, 3 and 4 respectively. Energy is consumed and expended more in the crushing plant than in the refinery plant. The best environment viable for vegetable oil production is to have a short distance as possible for raw materials and the use of diesel oil for firing boilers (scenario 2) as compared with Low Pour Fuel Oil (LPFO). It was recommended that study on environmental performance of vegetable oil production from different oil sources should be investigated in Nigeria, from cradle to grave.